1993
DOI: 10.1128/mcb.13.10.6336-6345.1993
|View full text |Cite
|
Sign up to set email alerts
|

Identification of AML-1 and the (8;21) Translocation Protein (AML-1/ETO) as Sequence-Specific DNA-Binding Proteins: theruntHomology Domain is Required for DNA Binding and Protein-Protein Interactions

Abstract: The AML1 gene on chromosome 21 is disrupted in the (8;21)(q22;q22) translocation associated with acute myelogenous leukemia and encodes a protein with a central 118-amino-acid domain with 69% homology to the Drosophila pair-rule gene, runt. We demonstrate that AML-1 is a DNA-binding protein which specifically interacts with a sequence belonging to the group of enhancer core motifs, TGT/cGGT. Electrophoretic mobility shift analysis of cell extracts identified two AML-1-containing protein-DNA complexes whose ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…It is also worth mentioning that a normal allele of RUNX1 is retained alongside RUNX1-ETO fusion gene in t(8;21) AML cells, 50 and that RUNX1-ETO is implicated in exerting opposing effects by competing with RUNX1 for binding to protein partners and to RUNX1-binding sites, but not affecting URE-PrPr interaction. 42,51,52 Collectively, our findings uncover heretoforeunknown cross-regulation and molecular interactions of lncRNAs with transcription factors and their oncogenic derivatives, providing mechanistic understanding underlying their molecular functions.…”
Section: Discussionmentioning
confidence: 71%
“…It is also worth mentioning that a normal allele of RUNX1 is retained alongside RUNX1-ETO fusion gene in t(8;21) AML cells, 50 and that RUNX1-ETO is implicated in exerting opposing effects by competing with RUNX1 for binding to protein partners and to RUNX1-binding sites, but not affecting URE-PrPr interaction. 42,51,52 Collectively, our findings uncover heretoforeunknown cross-regulation and molecular interactions of lncRNAs with transcription factors and their oncogenic derivatives, providing mechanistic understanding underlying their molecular functions.…”
Section: Discussionmentioning
confidence: 71%
“…To investigate the molecular mechanism of NLRP12 transcriptional regulation, potential transcriptional binding sites were screened within 800 bp on the NLRP12 promoter region using the JASPAR database for eukaryotic transcription factor (TF) binding profiles ( https://jaspar.genereg.net/ ). A conserved sequence motif (5′-TGTGGT/ACCACA-3′), recognized by a TF known as runt-related transcription factor 1 (RUNX1) ( 22 ) was found to have occurred 4 times ( Figure 2A ). Therefore, we evaluated the role of RUNX1 in the regulation of NLRP12 expression by generating luciferase reporter plasmid driven by 830 bp (pGL4: –830 to +90 NLRP12 ) of the NLRP12 promoter region containing 4 RUNX1-binding sites (NLRP12-Luc#1).…”
Section: Resultsmentioning
confidence: 99%
“…Runx2 response element in OC promoter was first identified in rat as an osteogenic tissue specific nuclear matrix protein binding site [Merriman et al, 1995] and in mouse as a osteoblast specific factor 2 binding site [Geoffroy et al, 1995], respectively. The binding sites of Runx2 and Runx1 have an identical core binding sequence [Bae et al, 1993, 1994; Meyers et al, 1993, 1995; Ogawa et al, 1993a,b]. However, it has not been reported that Runx3 binds directly to OSE2.…”
Section: Discussionmentioning
confidence: 99%